2022
DOI: 10.1101/2022.10.18.512804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent functions of two clades of flavodoxin in diatoms mitigate oxidative stress and iron limitation

Abstract: Phytoplankton rely on diverse mechanisms to adapt to the decreased iron bioavailability and oxidative stress-inducing conditions of today’s oxygenated oceans, including replacement of the iron-requiring ferredoxin electron shuttle protein with a less-efficient iron-free flavodoxin under iron limiting conditions. And yet, diatoms transcribe flavodoxins in high-iron regions in contrast to other phytoplankton. Here, we show that the two clades of flavodoxins present within diatoms exhibit a functional divergence,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…In addition to aiding in the elucidation of the diatom plastid-localized proteome, this study compared plastid-enriched proteomes collected from T. pseudonana cultures grown in both Fe-replete and Fe-limiting conditions to identify how the plastid proteome remodels under Fe-limitation. While previous analyses have shown that T. pseudonana has a limited inventory of canonical Fe-sensitive genes, including the lack of an Fe-sensitive isoform of flavodoxin (Graff van Creveld et al, 2023;Morrissey et al, 2015;Whitney et al, 2011), it was chosen for this study as it has a well-characterized Fe-limited transcriptome and whole-cell proteome (Mock et al, 2008;Nunn et al, 2013), a fully sequenced genome (Armbrust et al, 2004), and a plastid-targeted proteome containing 217 proteins (Schober et al, 2019). Within this study, we report the identification of 929 proteins within the plastid-enriched proteome of T. pseudonana across both Fe-limiting and Fe-replete conditions, expanding the inventory of proteins localized within the T. pseudonana plastid proteome.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to aiding in the elucidation of the diatom plastid-localized proteome, this study compared plastid-enriched proteomes collected from T. pseudonana cultures grown in both Fe-replete and Fe-limiting conditions to identify how the plastid proteome remodels under Fe-limitation. While previous analyses have shown that T. pseudonana has a limited inventory of canonical Fe-sensitive genes, including the lack of an Fe-sensitive isoform of flavodoxin (Graff van Creveld et al, 2023;Morrissey et al, 2015;Whitney et al, 2011), it was chosen for this study as it has a well-characterized Fe-limited transcriptome and whole-cell proteome (Mock et al, 2008;Nunn et al, 2013), a fully sequenced genome (Armbrust et al, 2004), and a plastid-targeted proteome containing 217 proteins (Schober et al, 2019). Within this study, we report the identification of 929 proteins within the plastid-enriched proteome of T. pseudonana across both Fe-limiting and Fe-replete conditions, expanding the inventory of proteins localized within the T. pseudonana plastid proteome.…”
Section: Introductionmentioning
confidence: 95%